# solving trig. equations

tan(3x) + 1 = sec(3x)

Thanks,

pretend 3x equals x
so tanx + 1 = secx
we know the law that 1 + tanx = secx
so tanx + 1 becomes secx
and... secx = secx
sec(3x) = sec(3x) [just put 3x back in for x- you don't really have to change 3x to x but it kinda makes it easier

Let 3x =u for simplicity sake
then tan u + 1 = sec u
sinu/cosu + 1 = 1/cosu
multiply by cos u
sin u + cos u = 1
square both sides
sin^2 u + 2(sinu)(cosu) + cos^2 u =1
but sin^A+cos^2Ax=1

so 1 + 2(sinu)(cos)=1
recall that sin(2A_=2sinAcosS

then sin 2u =0
or replacing the u
sin 6x = 0
by the CAST rule, 6x = 0,180º,360º
or 0, pi/2, pi in radians

so x = 0, 30º,60º or 0,pi/6,pi/3

The period of tan(3x)=180º or pi radians

eg. take the 60º answer, if we add 5*180 to it we get 960º
Left Side: tan (3*960) +1 = 0 + 1 = 1
Right Side: sec(3*960)= 1

sorry haley, that is wrong

tanx + 1 is not equal to secx
rather

tan^2 x + 1 = sec^2 x
see my solution below.

I forgot to include the following:

Since "squaring" took place in my solution, all answers should have been verfied.
Upon checking, we find that 30º does not work, since tan90º is undefined.
So all periodic answers based on 30º do not work

sin (u) + cos (u) = 1 --->

sqrt(2)sin(u+pi/4) = 1

Note that

sin(a+b) = sin(a)cos(b) + cos(a) sin(b)

You can use this rule to write a sum of sin and cos as a single sin or cos.

sin(u+pi/4) = 1/sqrt[2] --->

u = 0 Mod(2 pi) OR u = pi/2 Mod(2 pi)

In this case you could have found the two solutions u = 0 and
u = pi/2 by inspection. Because there can be only two solutions in an interval of 2 pi, you then know that these are all the solutions in such an interval. All other solutions differ from these by a multiple of 2 pi.

1. 👍 0
2. 👎 0
3. 👁 843

## Similar Questions

1. ### Calculus - Integration

Hello! I really don't think I am understanding my calc hw. Please help me fix my errors. Thank you! 1. integral from 0 to pi/4 of (tanx^2)(secx^4)dx It says u = tan x to substitute So if I use u = tan x, then my du = secx^2 then I

asked by Shelley on January 29, 2007
2. ### calculus

find dy/dx y=ln (secx + tanx) Let u= secx + tan x dy/dx= 1/u * du/dx now, put the derivative of d secx/dx + dtanx/dx in. You may have some challenging algebra to simplify it. Use the chain rule. Let y(u) = ln u u(x) = sec x + tan

asked by amy on March 9, 2007
3. ### Calc

Hello im trying to integrate tan^3 dx i have solved out the whole thing but it doesnt match up with the solution.. this is what i did: first i broke it up into: integral tan^2x (tanx) dx integral (sec^2x-1)(tanx) dx then i did a u

asked by UCI Student on May 30, 2012
4. ### Calc

Hello im trying to integrate tan^3 dx i have solved out the whole thing but it doesnt match up with the solution.. this is what i did: first i broke it up into: integral tan^2x (tanx) dx integral (sec^2x-1)(tanx) dx then i did a u

asked by ***UCI Student*** on May 30, 2012
5. ### Calculus

Int tanx sec^2x dx can be taken as (by putting it in form of Int xdx) Int secx.secx tanx dx=(sec^2x)/2 Int tanx.sec^2x dx=(tan^2)/2. Which one is correct and why is the difference?

asked by Anonymous on September 26, 2013
6. ### Math

Evaluate the integral of (secx)^2 * (tanx)^3 *dx I started out with letting u=secx and du=secx*tanx*dx , but then I am kind of stuck because I don't know how to factor out just secx*tanx? The answer in the book said that it is

asked by Dave on September 13, 2017
7. ### Pre-Cal

Perform the addition or subtraction. tanx - sec^2x/tanx tan^2(x)/tan(x) - sec^2x/tanx = tan^2x sec^2x / tanx then I use the identity 1+tan^2u=sec^2u I do not know what to do at this point.

asked by Hannah on March 5, 2010
8. ### Calculus

find the derivative of f(x)=tanx-4/secx I used the quotient rule and got (sec^2x-4)(secx)-(tanx-4)(cosx)/sec^2x but I'm pretty sure that's wrong. Help. Thanks.

asked by gnozahs on June 10, 2009
9. ### math

how does secx(tanx + tan^2x- sec^2x) simplified to sec x (tanx -1)?

asked by Jin on August 19, 2010
10. ### math

1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos s)=csc^2 s-csc s cot s 4. (secx/secx-tanx)=sec^2x+secxtanx 5. (cosx/secx-1)-(cosx/tan^2x)=cot^2x

asked by Tom on April 10, 2008

More Similar Questions